2017
DOI: 10.1159/000458442
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Associated Lung Cancer

Abstract: Lung cancer (LC) is one of the most common non-AIDS (acquired immune deficiency syndrome)-defining malignancies. It occurs more frequently in persons living with human immunodeficiency virus (PLWHIV) than in the HIV-negative population. Compared to their HIV-negative counterparts, patients are usually younger and diagnosed at more advanced stages. The pathogenesis of LC in PLWHIV is not fully understood, but immunosuppression in combination with chronic infection and the oncogenic effects of smoking and HIV it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
0
12
1
1
Order By: Relevance
“…The advent of ART has improved survival of HIV-infected adults and children leading to chronic illnesses such as different pulmonary diseases [ 7 , 8 ]. For instance, chronic obstructive pulmonary disease (COPD), asthma, pulmonary hypertension, lung cancer, and asthma are prevalent among HIV patients [ 7 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of ART has improved survival of HIV-infected adults and children leading to chronic illnesses such as different pulmonary diseases [ 7 , 8 ]. For instance, chronic obstructive pulmonary disease (COPD), asthma, pulmonary hypertension, lung cancer, and asthma are prevalent among HIV patients [ 7 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through the literature search in PubMed and Embase databases, we found a total of 923 individual records, but only 22 studies were considered possibly eligible and were evaluated by reading the full articles. [ 7 , 23 , 27 34 , 41 52 ] Ten studies were excluded because they did not assess the impact of HIV infection on the survival of lung cancer patients or they did not report data on the estimates of mortality risk associated with HIV infection. [ 7 , 23 , 45 52 ] At last, 12 studies were included into the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…HIV-infection status seems not to correlate with histotype and disease stage of LC [29,30] and, while controversial data in this regard have been reported [31], even more recent large cohort studies confirmed that distributions of the cancer stage at presentation and histologic subtypes are similar by HIV status [32,33].…”
Section: Lung Cancer Features In Hiv Infected Patientsmentioning
confidence: 94%